Uma relação entre dêixis e metadiscursividade - Cavalcante, Mônica Magalhães (2020)
In this paper, in order to examine the relations between deixis and metadiscoursive strategies of stance and engagement these forms play within the texts, we intend to analyze the effects of meaning created from the relation deixis-metadiscourse, by mainly considering the enunciative condition unique to deixis. With respect to deixis, we draw on author such as Bühler (1982[1934]), Benveniste (1988[1976]), Cavalcante (2000) e Ciulla (2002, 2008). For these authors, deictics would constitute elements that would indicate the origin point of the speaker, the origo of the enunciative situation, from which the interaction happens. With respect to metadiscourse, we mainly draw on Hyland (2005a, 2005b), in which we find the division between textual and interactional metadiscourse, with the marks referring either to more cotextual portions, or to relations between interlocutors. Moreover, the author presents various sublevels of stance and engagement. In this paper, following a method ological approach, we will specifically focus on marks of self mention and reader pronouns, which are subtypes of positioning and commitment, respectively, since they arise from essentially deictic marks, such as personal and possessive pronouns. We will show these marks in jokes available at “piadasnet.com”. We did not choose the text because of its theme or genre, but because of the in stances of deictic forms. We did not pay attention to the quantity of occurrences or its cases, but only to the effects of meaning the deixis-metadiscourse relation might exert upon the text under analyse. We assume the use of deictic forms might constitute different marks of metadiscourse and, for that reason, collaborates for the argumentative directing the speaker intends to give the text, since the marks of self mention and the reader pronouns are essentially formed by person deictics and that, at the same time, the use of these deictics shows a metadiscoursive aspect within the interaction between interlocutors, which both highlight and evoke its interlocutors inside enunciative situations. We also believe the types of deixis might be used as metadiscursive strategies and that, within these uses, these deictic forms cooperate to reinforce stances and to try to influence the other.